2019
DOI: 10.1093/ofid/ofz521
|View full text |Cite
|
Sign up to set email alerts
|

Interventions to Increase Completion of Hepatitis B Vaccination in People who Inject Drugs: A Systematic Review and Meta-analysis

Abstract: Increases in opioid misuse and injection drug use have resulted in a rise in acute cases of hepatitis B. We conducted a systematic review and meta-analysis of randomized studies to determine the effect (pooled odds ratio) of interventions to increase hepatitis B vaccination completion in people who inject drugs (PWID). Odds ratios from the included studies were combined to create a pooled odds ratio (OR) using the Inverse Heterogeneity Model. Eleven studies met the eligibility criterion of having a randomized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 20 publications
0
23
0
Order By: Relevance
“…The possibility that a high-pressure phase of CaSiO 3 might exist in the lower mantle was first suggested in 1967 in a study of CaSiO 3 -CaGeO 3 perovskite-type solid solution (2). In 1975, scientists successfully synthesized the CaSiO 3 -perovskite high-pressure phase with a cubic structure by using a laser-heated diamond anvil cell (3).…”
Section: Perovskite Retrieved From the Lower Mantlementioning
confidence: 99%
See 1 more Smart Citation
“…The possibility that a high-pressure phase of CaSiO 3 might exist in the lower mantle was first suggested in 1967 in a study of CaSiO 3 -CaGeO 3 perovskite-type solid solution (2). In 1975, scientists successfully synthesized the CaSiO 3 -perovskite high-pressure phase with a cubic structure by using a laser-heated diamond anvil cell (3).…”
Section: Perovskite Retrieved From the Lower Mantlementioning
confidence: 99%
“…Do they work? Studies suggest that payments were successfully used to increase vaccination for human papillomavirus in England (1), hepatitis B in the United States and United Kingdom (2), and tetanus toxoid in Nigeria (3). However, little is known about the effect of direct payment or lotteries on COVID-19 vaccination rates.…”
mentioning
confidence: 99%
“…A prior meta‐analysis showed that financial incentives, followed by accelerated vaccine schedules had the highest efficacy in helping the PWID to complete the scheduled 3‐dose vaccination series 57 . The newly available and equally efficacious Heplisav‐B vaccine which requires only two doses over only 1 month (vs 3 doses over 6 months) should be considered in this population to improve compliance and adherence 58 …”
Section: Gaps In Hbv Vaccination and Preventionmentioning
confidence: 99%
“…People who are homeless are half as likely as other groups to receive the influenza vaccination and people who use drugs or who sell sex are less likely to receive hepatitis B vaccination (HBV) than healthcare workers. [3][4][5] The reduced uptake is attributable to mental health issues, drug use and reduced access to primary healthcare, compounded by stigma and general distrust in authorities. 6 Intersecting vulnerabilities can pose additional barriers, with migration status among sex workers, for example, restricting access to vaccination programmes in Canada.…”
mentioning
confidence: 99%
“…Findings from a meta-analysis suggests that financial incentives and accelerated schedules were associated with 2.3 times the odds of completing HBV vaccination compared with standard care for people who use drugs. 5 Other review evidence shows that delivery of vaccinations via specialist services, such as OST clinics or needle syringe programmes, to hostels or shelters or outreach to places where drugs are used results in greater uptake of influenza and HBV vaccinations. 5 6 Emotional support and positive interactions in personal lives (defined as having someone to confide in or do something enjoyable with) has also been linked to increased completion of HBV vaccines among people experiencing homelessness.…”
mentioning
confidence: 99%